2021
DOI: 10.1155/2021/6611196
|View full text |Cite|
|
Sign up to set email alerts
|

Study on Collision Detection and Force Feedback Algorithm in Virtual Surgery

Abstract: The development of virtual reality technology is expected to solve traditional surgical training. The lack of methods has brought revolutionary advances in technology. The virtual surgery system based on collision detection and force feedback can enable the operator to have stronger interaction, which is an exploration of the feature of touch in virtual reality technology. Reality is an important indicator of the virtual surgical system. This article improves the realism of the system from the visual and tacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Linear regression was used for load forecasting. Zhang et al combined the ant colony algorithm with gray theory; the gray ant colony neural network is established, and the feedback algorithm is added on the basis of the GM (1,1) model, after which the unique advantages of the two can be exerted, and the expected results can be obtained [2]. Chen and Chen used autoregressive modeling to develop a method based on nonlinear load regression and modifed it with chaos theory, successfully reducing the infuence of local extreme values on the prediction results [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Linear regression was used for load forecasting. Zhang et al combined the ant colony algorithm with gray theory; the gray ant colony neural network is established, and the feedback algorithm is added on the basis of the GM (1,1) model, after which the unique advantages of the two can be exerted, and the expected results can be obtained [2]. Chen and Chen used autoregressive modeling to develop a method based on nonlinear load regression and modifed it with chaos theory, successfully reducing the infuence of local extreme values on the prediction results [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared with traditional surgical training, virtual surgery system constructs an authentic and highly interactive virtual environment to enhance the efficiency and effectiveness of surgery learning and training [1,24]. With the introduction of collision detection, real-time image and haptic feedback, the immersion of VR-based virtual surgery system has been further improved [12][13][14]. Previous studies have confirmed that VRbased simulators with or without force feedback support effective learning reified as faster completion of surgery and less injury [20,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In order to fulfill natural physician-computer interaction, gesture recognition, the technology that recognizes the hand gestures of users directly in the virtual environment and generates various image feedbacks according to the gestures [6][7][8], has great potential in the field of medicine including rehabilitation, imageology and education [9][10][11]. In virtual surgery, the collision detection (CD) is indispensable, which used to detect whether there is overlap between one or more geometric objects in space [12]. The contact among the virtual hand, scalpel and tissue needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Also, immersive technology has enabled 3D visualization of information and facilitated information communication and understanding for purposes such as informed purchase decision making, learning and teaching, and participatory design. For instance, a recent study (Zhang et al, 2021) on virtual surgical training systems enabled by modern medical technologies and VR shows that the design of collision detection and force feedback algorithms is essential to ensure transparency and immersion for trainees. The Virtual Experiences Laboratory (VXLab) at RMIT University visualized time series data as static images, and the solar wind imagery in a looping video format, providing an immersive space science experience for students that fosters learning, cooperation and "transparent data sharing" (Carter et al, 2022).…”
Section: Technology: Enhance or Inhibit Transparencymentioning
confidence: 99%